STRATEGI KOMUNIKASI PEMASARAN TERPADU UNTUK MENINGKATKAN BRAND AWARENESS PADA THE TRANS RESORT BALI - Komang Alicia Trisnayanti; I Made Widiantara, Ni Ketut Suciani (ADISAM PUBLISHER, 2025)
Tourism is one of the main pillars of Bali’s regional economy, which drives intense competition in the hospitality accommodation sector. This study discusses the implementation of integrated marketing communication (IMC) strategies to enhance brand awareness at The Trans Resort Bali. A qualitative study case approach was applied using SWOT analysis. The results show that the total score of IFAS Matrix is 2.87, while the EFAS Matrix scored 2.92, placing the company in Quadrant I, a position that supports aggressive strategies to continue growing and strengthening brand awareness among its audience. In terms of industry attractiveness, the company is positioned in Cell 5 (Growth Stability), indicating that The Trans Resort Bali is experiencing stable growth and that its current strategy remains relevant. Following technological developments and the expansion of its target market, the company must maintain and even improve its market position to achieve its vision, mission, goal and profitability. The main strengths of The Trans Resort Bali lie in its strategic location, high- quality facilities and services and an integrated marketing communication strategy, both directly (e.g., sales visits) and directly (e.g., digital media channels). However, eflorts to build engagement through advertising have not been fully optimized. Recommended strategies include strengthening high quality social media content through organic posts, collaborating with influencers or travel bloggers, optimizing and maintaining consistency in digital advertising via Meta Ads and Google Ads and organizing promotional events supported by media partners. There strategies are expected to increase brand visibility, recall and positive brand image in the minds of potential guests and loyal customers of The Trans Resort Bali